Ultrasound elastography score and strain index in different parathyroid lesions - Bekir Cakir (Endocrine Connections, 2019)
Background: Despite significant improvement in imaging quality and advanced scientific knowledge, it may still sometimes be difficult to distinguish diff erent parathyroid lesions. The aims of this prospective study were to evaluate parathyroid lesions with ultrasound elastography and to determine whether strain index c an help to differentiate parathyroid lesions. Methods: Patients with biochemically confirmed hyperparathyroidism and l ocalised parathyroid lesions in ultrasonography were included. All patients underwent B-mode US and USE examination. Ultrasound elastography scores and strain index of lesions were determined. Strain index was defined as the ratio of strain of t he thyroid parenchyma to the strain of the parathyroid lesion. Results: Data of 245 lesions of 230 patients were analysed. Histopathologically, there were 202 (82.45%) parathyroid adenomas, 26 (10.61%) atypical parathyroid adenomas, and 17 (6.94%) cases of parathyroid hyperplasia. Median serum C a was significantly higher in atypical parathyroid adenoma patients than parathyroid hyperplasia patients (P = 0.019) and median PTH was significantly higher in APA compared to PA patients (P < 0.001). In 221 (90.2%) of the parathyroid lesions, USE score was 1 or 2. The median SI of atypical parathyroid adenomas was significantly hig her than parathyroid adenomas and hyperplasia lesions (1.5 (0.56–4.86), 1.01 (0.21–8.43) and 0.91 (0.26–2.02), respectively, P = 0.003). Conclusion: Our study revealed that SI of parathyroid lesions as well as s erum calcium, parathyroid hormone levels, and B-mode US features may help to predict the atypical parathyroid adenoma. Ultrasound elastography can be used to diff erentiate among parathyroid lesions and guide a surgical approach.